PENGGUNAAN PENGAYA (ADD-ON) AUTOCRAT PADA GOOGLE SHEETS DALAM APLIKASI SERING CUTI - SYAEFUDIN, ROCHMAT ALI; Suseno, Wahyu Hanggoro (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
The use of information technology in the government administration is carried out to realize good governance. The use of information systems enables the automation of work and service functions including for human resource administration. Administration of employee leave at the Politeknik Kesehatan Kementerian Kesehatan Surakarta still running manually. Employees who will take leave apply it manually and often cause problems because the application not in accordance with the provisions, among others are the misidentification of the authorized official to provide leave which makes the administration of employee leave ineffective. Sering Cuti using free Google facilities which easy to learn and can be easily used by employees and Autocrat add-on. This add-on processes mail merge the employee leave data, converting into filled application form and sends directly to the employee's e-mail address. Autocrat uses in the Sering Cuti has made it easier to administer and reduce errors in employee leave applications. Sering Cuti can be accessed by employees easily and apply for employee leave anywhere online.